Understanding the relationship between social determinants of health and maternal mortality - Jones, GL; Mitchell, C; Hirst, J; Anumba, DOC (Wiley, 2022)
Within this document we use the terms pregnant woman and women's health. However, it is important to acknowledge that it is not only people who identify as women for whom it is necessary to access care. Obstetric and gynaecology services and delivery of care must therefore be appropriate, inclusive and sensitive to the needs of those individuals whose gender identity does not align with the sex they were assigned at birth.